2016
DOI: 10.1371/journal.pone.0154807
|View full text |Cite|
|
Sign up to set email alerts
|

Virtual Hand Feedback Reduces Reaction Time in an Interactive Finger Reaching Task

Abstract: Computer interaction via visually guided hand or finger movements is a ubiquitous part of daily computer usage in work or gaming. Surprisingly, however, little is known about the performance effects of using virtual limb representations versus simpler cursors. In this study 26 healthy right-handed adults performed cued index finger flexion-extension movements towards an on-screen target while wearing a data glove. They received each of four different types of real-time visual feedback: a simple circular cursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
9
0
3
Order By: Relevance
“…Similarly, visual augmentation by marking fingers that have to move together to produce symmetric or parallel tapping patterns does not affect performance 45 . Moreover, previous studies have suggested that movement execution is modulated by the level of abstraction of visual effector feedback 46 , 47 . Our study did not abstract visual direction information, but, through the mirror setup, provided participants with visual feedback that appeared to reflect the real hands.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, visual augmentation by marking fingers that have to move together to produce symmetric or parallel tapping patterns does not affect performance 45 . Moreover, previous studies have suggested that movement execution is modulated by the level of abstraction of visual effector feedback 46 , 47 . Our study did not abstract visual direction information, but, through the mirror setup, provided participants with visual feedback that appeared to reflect the real hands.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, we previously experimented on adults comparing different forms of online feedback during visually guided finger movements in a finger-reaching task. We found that providing hand, virtual hand (VH) or shadow hand (SH) instead of point light (PL) or cursor (CU) feedback resulted in significantly faster movement initiation for three out of the four comparisons (not for VH vs. PL; Brand et al, 2016 ). Hence, the results of our previous study suggested that hand feedback might play an important role in visually guided movement control and in its underlying brain processes.…”
Section: Introductionmentioning
confidence: 89%
“…The experiment setup is visualized in Figure 1 . Parts of the setup have previously been described in our previous study (Brand et al, 2016 ). The experiment was performed with subjects lying in a wide bore (70 cm diameter) magnetic resonance scanner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, visual augmentation by marking fingers that have to move together to produce symmetric or parallel tapping patterns does not affect performance (Mechsner, 2004). Moreover, previous studies have suggested that movement execution is modulated by the level of abstraction of visual effector feedback (Brand et al, 2016;Veilleux & Proteau, 2010). Our study did not abstract visual direction information, but, through the mirror setup, provided participants with visual feedback that appeared to reflect the real hands.…”
Section: Discussionmentioning
confidence: 70%